ANALYSIS OF THE ECONOMIC PERFORMANCE IN SITUBONDO REGENCY (2009 â€“ 2013) - Kurniawan, Alif Imansyah (Jurnal Ilmiah Mahasiswa FEB, 2016)
By using secondary data from Gross Regional Domestic Product (GRDP) of Situbondo Regency and East Java Province in 2009 to 2013 based on constant priceÂ  obtained from Central Bureau of Statistics (BPS) and Location Quotient Analysis and Shift Share, this study is aimed to analyze the economic performance in Situbondo Regency in 2009 to 2013. The results of the analysis using the method of Location Quotient (LQ), two sectors that are included in the basic sector (LQ> 1) of Situbondo Regency are the agriculture and trade sectors, hotels and restaurants. Whereas the results of the calculations using shift share analysis show three sectors that are categorized in the competitive sectors, including agriculture, manufacturing and services sectors. All three sectors indicate a faster growth than the same economic sectors in East Java province. Thus, they have a high competitiveness and the potential to be developed to encourage the economic growth in Situbondo Regency.Keywords: Economic Growth, Analysis Location Quotient and Shift Share